COVID-19 and policies for care homes in the first wave of the pandemic in European welfare states: Too little, too late?. (February 2022) - Daly, Mary; León, Margarita; Pfau-Effinger, Birgit; Ranci, Costanzo; Rostgaard, Tine
This article examines COVID-19 and residential care for older people during the first wave of the pandemic in 2020, comparing a range of countries – Denmark, England, Germany, Italy and Spain – to identify the policy approaches taken to the virus in care homes and set these in institutional and policy context. Pandemic policies towards care homes are compared in terms of lockdown, testing and the supply of personal protective equipment. The comparative analysis shows a clear cross-national clustering: Denmark and Germany group together by virtue of the proactive approach adopted, whereas England, Italy and Spain had major weaknesses resulting in delayed and generally inadequate responses. The article goes on to show that these outcomes and country clustering are embedded in particular long-term care (LTC) policy systems. The factors that we highlight as especially important in differentiating the countries are the resourcing of the sector, the regulation of LTC and care homes, and the degree of vertical (and to a lesser extent horizontal) coordination in the sector and between it and the health sector.